MODEL ANALYSIS OF FREIGHT TRANSPORTATION MODE CHOICE BETWEEN TRAIN AND TRUCK (CASE STUDY: PEMATANG SIANTAR-BELAWAN ROUTE) - Sintindaon (NIM : 25098028), Charles
Abstract : This study emphasizes in freight transportation, which has unbalanced market between train mode and truck mode. The customers interest to choose train mode is lower than truck mode. For that reason, it is important to understand freight customers behaviour. This research develops freight transportation model particularly agricultural commodity transportation from Pematang Siantar to Belawan. The approach used in this research is a stated preference (SP) technique. First at key factors that influence the mode choice for agricultural commodity transportation we identified. Then customers responses were gathered using SP questionnaire. Base on these response data we develop a model which explain of freight transportation mode choice behaviour, carry out sensitivity analysis of mode substitution influenced by service and expedition attributes. Analysis result by maximum likelihood method shows that safety factor is the primary factor for foreign destination. For domestic destination, cost and time factor is the primary factor. Meanwhile regression analysis shows that safety and cost factor is primary factor for foreign destination. For domestic destination, cost and time factor is the primary factor. Another key factor that must be considered is station accessibility. Study on Pematang Siantar-Belawan with toll road scenario gives probability that truck mode users will increase 22.5% (maximum likelihood method) and 26.5% (regression analysis method). Study on double track scenario gives probability that train mode users will increase 15% (maximum likelihood method) and 12% (regression analysis method). This result is anticipated as an instrument to determine freight transportation strategic planning policy, especially train transportation in North Sumatra Region.